2017
DOI: 10.18321/ectj667
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phytohormones on Monosaccharide Composition of Polysaccharides from Wheat Suspension Culture

Abstract: Plant polysaccharides with technical and physiologic traits attract researchers by their high physiological activity in regulation of the growth, development and protective reactions. Cell cultures allow to regulate chemical composition of synthesized substances by changing media composition and are widely used to enhance or change the biosynthesis of metabolites. The aim of this study was to investigate the influence of phytohormones 2,4-dichlorphenoxyacetic acid (2,4 –D) and abscisic acid (ABA) of culture me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We predicted that this approach would allow us to verify the putative involvement of some vital biochemical pathways, including the methionine cycle [53] and its crucial compound S-adenosyl-L-methionine (SAM), in DNA methylation [54], which could contribute to SV [19]. Moreover, we suspected that compounds indicative of stress caused by in vitro culture, such as lipids [55], polyamines [56], and polysaccharides [57], might also affect DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that this approach would allow us to verify the putative involvement of some vital biochemical pathways, including the methionine cycle [53] and its crucial compound S-adenosyl-L-methionine (SAM), in DNA methylation [54], which could contribute to SV [19]. Moreover, we suspected that compounds indicative of stress caused by in vitro culture, such as lipids [55], polyamines [56], and polysaccharides [57], might also affect DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The T-fractions were revealed to be less toxic for normal cells in the concentrations inhibiting 50% or more of colon cancer cells. This is interesting because previous work [ 33 ] suggested that polysaccharides from ABA treated wheat cells (specifically the A-b fraction) were quite different from those from 2,4-D treated cells (specifically the T-010-fraction). Indeed, the A-b fraction was enriched in glucose, probably from β-glucans, compared to the T-010 fraction which had a monosaccharide composition suggestive of a more equal mixture of arabinogalactans, glucuronarabinoxylans, β-glucans, and xyloglucans (see Supplementary Data, Figure S1A ).…”
Section: Discussionmentioning
confidence: 85%
“…Cell suspension cultures of soft spring wheat Triticum aestivum of the Kazakhstanskaya 10 variety (provided by Kazakh Research Institute of Agriculture and Plant Growing, Almaty, Kazakhstan) were grown in two types of Murashige and Skoog (MS) [ 37 ] liquid medium (Sigma-Aldrich, St. Louis, MO, USA) as we described before [ 33 ] with the addition of phytohormones which are commonly used in plant biotechnology to regulate morphogenesis and biosynthesis of secondary bioactive metabolites in vitro [ 38 , 39 , 40 , 41 ]: 5.0 mg/L 2,4-D—2,4-dichlorophenoxyacetic acid (Sigma-Aldrich, St. Louis, MO, USA) and 1.0 mg/L ABA—abscisic acid (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations